PENGGUNAAN TEKNIK TIME OUT DALAM MENGENDALIKAN EMOSI ANAK USIA DINI - Aisyah Fadilah (CV Sintesia, 2023)
The emotional development of Kindergarten (TK) children is very strong, in this phase children cannot control their emotions so that kindergarten children (TK) often show emotional outbursts. Often we can found the children running amok to express negative emotions. They scream, kick and beat so that it is difficult to control, be guided and directed by the teacher and it affected to the class situation. For this reason, there is a need to control emotions and how to respond to children's emotions appropriately so as not to cause other problems and as a class management effort. The purpose of this study in general is to control the emotions of early childhood through Time Out Technique at Istiqamah Kindergarten Bandung.The spesific of this study are (1) To describe preparations or pre-Time Outs in an effort to control the emotions of early childhood at Istiqamah Kindergarten. (2) To describe the implementation strategy or steps of Time Out in an effort to control the emotions of early childhood at Istiqamah Kindergarten. (3) To describe the results of Time Out in an effort to control the emotions of Early Childhood at Istiqamah Kindergarten. The method used is descriptive with a qualitative approach. Data collection techniques used in this study are observation, interview, documentation, literature study and triangulation. The subject of this research is the teacher and student group A Istiqamah Kindergarten Bandung. The study have the results: 1) PraTime Out in Time Out techniques at Istiqamah kindergarten basically the teacher already has their understanding of children's emotional development, the technique of using Time Out and how to condition children in using Time Out techniques.2) The implementation of the Time Out technique was carried out by the teacher of group A when the child was unable to control emotions, not obeying the rules agreed upon when conditioning before Time Out or other negative emotions, carried out in the classroom by placing the child in a quiet chair prepared by the teacher for several minutes or several counts.3) The results of using the Time Out technique have been achieved well in order to control the emotions of early childhood. Children are more emotionally controlled and can obey the rules. Based on the findings, it is recommended that PAUD Institutions can be advised to increase teachers'competence by participating in relevant training or if the institution does not allow to bring special speakers and competent in mastering Time techniques, the teacher should always upgrade understanding and abilities in emotional development of early children and use of Time Out techniques. For parents, they should collaborate with the teacher in developing aspects of their child's development, especially their emotional development in the parenting program.